THE EFFECT OF HEALTH EDUCATION USING AUDIOVISUAL MEDIA ON THE KNOWLEDGE AND ATTITUDE SCORES ABOUT PRE-HOSPITAL STROKE MANAGEMENT IN FAMILIES - yusniawati, yustina ni putu; Novi Cahyani, Ni Luh Putu (Nurse and Health: Jurnal Keperawatan, 2025)
ABSTRACT Background: Health education about pre-hospital stroke management in families is very important. One of the medias that can be used in providing health education about pre-hospital stroke management is the audiovisual media. Purpose: The purpose of this study was to find out the effect of health education with audiovisual media on family knowledge and attitudes about pre-hospital stroke management. Methods: This study employed a pre-experimental design with one group pre-test and post-test design. The population in the study were families who lived and cared for the elderly (caregivers). The sample in this study were 33 respondents who were selected through simple random sampling. The instrument used in this study was a questionnaire. The statistical test used to analyze the data was the Wilcoxon Rank Test. Results: The results showed that the average pre-test score of knowledge was 3.09, the median post-test score of knowledge was 6, the median pre-test score of attitudes was 28, the median post-test score of attitudes was 30, and the statistical test results obtained the p-value = 0.001. Conclusion: There is an effect of health education with audiovisual media to the knowledge and attitudes of the families about pre-hospital stroke management. The health workers, particularly those working at the public health center should consider using audiovisual as a medium to provide health education to the community.